(untitled) (Research, Society and Development, 2021)
This work aims to investigate the association between geriatric depression and oral self-perception, assessing functional scales, socioeconomic determinants, and normative oral conditions. The study was based on an inductive approach, with statistical procedures and descriptive technique using direct observation with 250 elders enrolled at the Reference Center, located in João Pessoa, Paraíba, Northeastern Brazil. Data collection was carried out focusing on a socioeconomic survey. A clinical examination was performed to obtain data on DMFT, edentulism, the need and use of prosthesis, and oral lesion. GOHAI, Pfeffer, Katz and Geriatric Depression Scales (GDS-15) were made. The elders were mostly illiterate women, from 60 to 70 years old, with low income. The average DMFT was 28.17, and edentulism was perceived in 55.2%. Oral self-perception was unfavorable for 87.2%, depressive symptoms affected 33.2% of individuals and functional dependence was noticed in 9.2%. The Katz and Pfeffer scales were statistically associated with the GDS-15 scale (p<0.05). The depressive symptoms were associated with the female gender, illiterate condition, and poor food intake after binary regression. However, they are not associated with normative oral conditions and oral self-perception in non-institutionalized elders in Northeastern Brazil.